2020
DOI: 10.31661/jbpe.v0i0.2003-1080
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach to Automatic Recognition of Arcus Senilis

Abstract: Background: Arcus Senilis (AS) appears as a white, grey or blue ring or arc in front of the periphery of the iris, and is a symptom of abnormally high cholesterol in patients under 50 years old. Objective: This work proposes a deep learning approach to automatic recognition of AS in eye images. Material and Methods: In this analytical study, a dataset of 191 eye images (130 normal, 61 with AS) was employed where ¾ of the data were used for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We therefore performed several sensitivity analyses and found similar results. Amini and Ameri proposed a deep learning based automatic recognition of corneal arcus [ 38 ]. Their model achieved a high accuracy in classifying images with and without arcus.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore performed several sensitivity analyses and found similar results. Amini and Ameri proposed a deep learning based automatic recognition of corneal arcus [ 38 ]. Their model achieved a high accuracy in classifying images with and without arcus.…”
Section: Discussionmentioning
confidence: 99%
“…Iridology is a technique that was discovered more than a century ago to discover information about a person's health by evaluating iris features such as color or pattern [1], [2]. The high level of cholesterol in the human body is one of the disorders that are identifiable using the iridology approach [3].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) is becoming more appealing for medical applications, enabling for the exploration of new areas where computer algorithms might improve medical operations [9]- [12], also recent world-wide disease namely COVID-19 that has been declared as a pandemic by the World Health Organization on 11 th March 2020 [13]- [16]. Recent studies have demonstrated the potential of various non-invasive techniques in detecting cholesterol from the images of iris [1], [17]- [21], skin [22], [23], MRI [24], and hand pattern [25]. Most of these methods are based on ML algorithms that extract all the image features before training the dataset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation